The duality of profiles teachers advisers in the academic context: associated implications (Research, Society and Development, 2023)
The objective of this study was to analyze the profiles of mentoring professors in the postgraduate context. It was a descriptive, exploratory study, with a qualitative approach, analyzed according to the inductive thematic analysis. A semi-structured and audio-recorded interview was conducted with 38 master's and 35 doctoral students, linked to a stricto sensu postgraduate program in the health area, at a brazilian public university, of which 14 reported implications associated with the guidance of professors. From this, a category called: “The duality of profiles of guiding professors in the academic context” and two subcategories were constructed: “The profile of guiding professors who effectively guide” and “The profile of tutors with unsatisfactory and/or inadequate guidance”. It was found that professionals with a more empathetic profile, who offer support and guide the development of the research, corroborate for a more pleasant journey and enable the construction of bonds. However, tutors who do not guide the student, or provide unsatisfactory and/or inadequate guidance, hierarchize the relationship, hinder communication through distance and imposed barriers, making the academic development process extremely difficult. Furthermore, significant emotional repercussions are also triggered in the student's life resulting from this relationship. It is essential that mentoring teachers seek to effectively guide their students, confirming their intellectual, social and affective commitment. Thus, these professionals can develop successful scientific productions and, consequently, express their positive and humanized legacy, through emotional care and quality in teaching and research for future teachers and researchers in the country.